Concurrent undernutrition and overnutrition within indian families between 2006 and 2021 - Dwivedi, Laxmi Kant; Puri, Parul; Pant, Anjali; Chauhan, Alka; Scott, Samuel P.; Sigh, Shrikant; Pedgaonkar, Sarang; Nguyen, Phuong Hong (Elsevier, 2023)
Background The double burden of malnutrition (DBM), characterized by concurrent undernutrition and overnutrition, is a growing global concern. Families share resources and eating behaviors and programs often target households, yet evidence of the DBM at the family level is scarce. Objectives This study examined trends and inequality in the intrahousehold DBM in India between 2006 and 2021. Methods Data were from 3 waves of India’s National Family Health Survey (NFHS 2006, 2016, and 2021). We examined 3 types of household member (with children aged <5 y) combinations: mother–child (N = 328,039 across 3 waves), father–child, and parent (mother and father)–child (N = 47,139 for each pair). The DBM was defined as one or more individuals with undernutrition (either wasting or stunting in children or underweight in adults) and one or more overweight individuals within the same household. DBM was examined over time, at national and subnational levels, and by residence and wealth. Results Nearly all DBM was in the form of an overweight parent and an undernourished weight or stunted child. The prevalence of parent–child DBM increased from 15% in 2006 to 26% in 2021. Father–child pairs experienced the most rapid DBM increase, from 12% in 2006 to 22% in 2021, an 83% increase, driven by increasing overweight among men. In 2021, the DBM was highest in North-Eastern and Southern states, and among relatively rich households from urban areas. The increase in the DBM was faster in rural areas and among poor households compared with that in urban areas and rich households. Urban–rural and rich–poor inequalities in the DBM have decreased over time. Conclusions The intrahousehold DBM has increased over time, affecting 1 in 4 households in India in 2021. Family-based interventions that can simultaneously address child underweight and parent overweight are required to address India’s increasing intrahousehold DBM.